2014
DOI: 10.1038/ncomms4430
|View full text |Cite
|
Sign up to set email alerts
|

HACE1-dependent protein degradation provides cardiac protection in response to haemodynamic stress

Abstract: The HECT E3 ubiquitin ligase HACE1 is a tumour suppressor known to regulate Rac1 activity under stress conditions. HACE1 is increased in the serum of patients with heart failure. Here we show that HACE1 protects the heart under pressure stress by controlling protein degradation. Hace1 deficiency in mice results in accelerated heart failure and increased mortality under haemodynamic stress. Hearts from Hace1−/− mice display abnormal cardiac hypertrophy, left ventricular dysfunction, accumulation of LC3, p62 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…It is generally agreed that ubiquitin conjugation to substrates drives the retro‐translocation process and transfers the ubiquitinated substrates to the cytosolic 26S‐proteasome for digestion. Thus, levels of ubiquitin‐conjugated proteins can reflect the activity of degradation (Su and Wang, ; Zhang et al , ). As shown in Figure A and Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally agreed that ubiquitin conjugation to substrates drives the retro‐translocation process and transfers the ubiquitinated substrates to the cytosolic 26S‐proteasome for digestion. Thus, levels of ubiquitin‐conjugated proteins can reflect the activity of degradation (Su and Wang, ; Zhang et al , ). As shown in Figure A and Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by Zhang et al (22) and Rotblat et al (28) showed that a homolog to the E6-AP carboxyl terminus domain and HACE1 is required for modulating stress responses in the heart and brain via autophagy. Deleting the Hace1 gene resulted in reduced autophagy flux in a p62-dependent manner in a severe transaortic constricted (sTAC) mouse heart, suggesting that HACE1 is critical in mediating p62-dependent autophagy flux in myocytes (22). We investigated PLN levels in Hace1-null mice.…”
Section: Resultsmentioning
confidence: 99%
“…An important component in maintaining proteostasis is the rapid digestion of mis-folded species. While autophagy plays a role in this process, particularly under certain pathological conditions such as heart failure (3), the bulk of this “janitorial function” in healthy cells is mediated by the proteasome (4). Low levels of proteasome activity exacerbate protein-folding diseases, while higher proteasome activity ameliorate them (514).…”
Section: Introductionmentioning
confidence: 99%